Looking Back to Move Forward: The Next Decade and Beyond for Human Experience - Jason Wolf (The Beryl Institute, 2024)
This issue comes out at an important moment for the experience conversation. It was ten years ago from the publication date of this issue on April 30, 2014, that the first issue of Patient Experience Journal (PXJ) was released. PXJ was intended to be a gathering place. A virtual town square for the experience movement where people could and would come together to share ideas and proven practice. This value of collaboration is at the foundation of our very efforts as a global community through The Beryl Institute. Experience is not some secret competitive ingredient in the world of healthcare. It is a promise we make to one another - to what matters to patients, to the needs of the healthcare workforce, to the realities faced by the communities that healthcare serves. What sparked us to start this effort over a decade ago is what continues to inspire us on the journey of where we go from here.